Penerapan model Pembelajaran Project Based Learning Berbantuan Video Animasi dalam Meningkatkan Kemampuan Pemecahan Masalah pada Pelajaran IPAS kelas X - Fridollin Fridollin; Wahyuni Oktavia; Resy Nirawati (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the application of the Project Based Learning (PjBL) model assisted by animated videos in improving problem-solving skills in Natural and Social Sciences (IPAS) subjects. The study used a quasi-experimental approach with a one-group pretest and posttest design. The subjects were 30 fifth-grade elementary school students selected as samples. The research instruments included a problem-solving ability test and an observation sheet for the implementation of learning. The results showed a significant increase in students' problem-solving skills after being treated through the PjBL model assisted by animated videos. The average posttest score was higher than the pretest, so it can be concluded that this learning strategy is effective in improving student learning outcomes. The use of animated videos helped students to visualize abstract concepts and engage more actively in the learning process. In addition, the results of observations of the implementation of learning showed that students became more active, enthusiastic, and able to work together in groups to complete the project. Student activity increased gradually, starting from the project planning stage, information collection, to the presentation of results. The teacher acted as a facilitator who provided direction and guidance, while students were directly involved in each process. This indicates that the integration of technology-based media supports collaborative and student-centered learning. Therefore, the implementation of the Project-Based Learning model with animated videos is not only effective in improving problem-solving skills but also fosters overall student engagement in science learning. Therefore, this learning model can be recommended as an innovative strategy to enhance problem-solving skills in primary education.